2017
DOI: 10.1186/s12974-017-0889-3
|View full text |Cite
|
Sign up to set email alerts
|

Acute neuroinflammation induces AIS structural plasticity in a NOX2-dependent manner

Abstract: BackgroundChronic microglia-mediated inflammation and oxidative stress are well-characterized underlying factors in neurodegenerative disease, whereby reactive inflammatory microglia enhance ROS production and impact neuronal integrity. Recently, it has been shown that during chronic inflammation, neuronal integrity is compromised through targeted disruption of the axon initial segment (AIS), the axonal domain critical for action potential initiation. AIS disruption was associated with contact by reactive infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 84 publications
(134 reference statements)
3
44
0
Order By: Relevance
“…Gram negative bacteria of gastro-intestinal tract secrete LPS that exerts proinflammatory actions on neurons [15]. Animal studies showed that LPS increases neuroinflammation by NOX2 activation [15,25,26]; however, the mechanism through which LPS damages the nervous system is unclear. LPS has been hypothesized to have a pathogenetic role in PANDAS [27], although no study evaluated LPS serum levels in this neuropsychiatric disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Gram negative bacteria of gastro-intestinal tract secrete LPS that exerts proinflammatory actions on neurons [15]. Animal studies showed that LPS increases neuroinflammation by NOX2 activation [15,25,26]; however, the mechanism through which LPS damages the nervous system is unclear. LPS has been hypothesized to have a pathogenetic role in PANDAS [27], although no study evaluated LPS serum levels in this neuropsychiatric disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Gram negative bacteria of gastro-intestinal tract secrete LPS that exerts proinflammatory actions on neurons [15]. Animal studies showed that systemic LPS administration increases neuroinflammation by NOX2 activation [15,25,26]; however, the mechanism through which LPS damages the brain is unclear.…”
Section: Ros Derived From Nox-2 Activation Leads To Inflammation In Smentioning
confidence: 99%
“…Gram negative bacteria of gastro-intestinal tract secrete LPS that exerts pro-inflammatory actions on neurons [15]. Animal studies showed that systemic LPS administration increases neuroinflammation by NOX2 activation [15,25,26]; however, the mechanism through which LPS damages the nervous system is unclear.…”
Section: Ros Derived From Nox-2 Activation Leads To Inflammation In Smentioning
confidence: 99%